2013
DOI: 10.1176/appi.ps.201200142
|View full text |Cite
|
Sign up to set email alerts
|

Telephone Monitoring and Support After Discharge From Residential PTSD Treatment: A Randomized Controlled Trial

Abstract: Telephone care management had little incremental value for patients who were already high utilizers of mental health services. Telephone care management could potentially be beneficial in settings where patients experience greater barriers to engaging with outpatient mental health care after discharge from inpatient treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 52 publications
3
45
0
Order By: Relevance
“…This interpretation is consistent with the finding that, of the 3 previous randomized clinical trials of collaborative care for PTSD, only the intervention with an evidence-based psychotherapy component had a significant treatment effect. 25,26,28,29 Although pharmacotherapyfocused collaborative care has been shown to be effective for depression, [47][48][49] these results suggest that the larger effect size associated with collaborative care models that have pharmacotherapy and psychotherapy components 50 is needed to improve PTSD outcomes among veterans. Our findings suggest that collaborative care models can encourage veterans to initiate and adhere successfully to evidencebased psychotherapies for PTSD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This interpretation is consistent with the finding that, of the 3 previous randomized clinical trials of collaborative care for PTSD, only the intervention with an evidence-based psychotherapy component had a significant treatment effect. 25,26,28,29 Although pharmacotherapyfocused collaborative care has been shown to be effective for depression, [47][48][49] these results suggest that the larger effect size associated with collaborative care models that have pharmacotherapy and psychotherapy components 50 is needed to improve PTSD outcomes among veterans. Our findings suggest that collaborative care models can encourage veterans to initiate and adhere successfully to evidencebased psychotherapies for PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…27 A trial conducted among 195 primary care patients at 4 large urban VAMCs 28 found no differences in PTSD outcomes between veterans randomized to collaborative care and UC. Another trial conducted among 355 veterans discharged from residential PTSD treatment 29 also failed to show a clinical benefit of collaborative care. In addition to the differences between civilian and veteran populations in these trials, an important distinction between the interventions tested is that only the one tested by Zatzick et al 25,26 specifically facilitated the delivery of evidence-based psychotherapy in addition to optimizing pharmacotherapy.…”
mentioning
confidence: 99%
“…Several studies show positive effects, but sometimes only in certain subgroups, typically the more severe patients who make poorer initial progress in treatment (1012,14). However, two recent studies produced negative results (13,15). Studies support the use of IVR and PDA technology to conduct assessments, but there are few data on whether IVR- or PDA-based interventions produce better substance use outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Over a 12-month follow up, there were no differences between the two conditions on self-report measures of PTSD symptoms, alcohol use, drug use, or depression (15). The authors noted that the TAU control condition had surprisingly good outcomes, which reduced the likelihood of showing an effect.…”
Section: Telephone-based Interventionsmentioning
confidence: 99%
“…Indeed, among telephone-monitored patients, 60%, 64%, and 54% received continuing mental health outpatient care at the 3-, 9-, and 15-month follow-ups, respectively; among usual care patients, corresponding percentages were 65%, 63%, and 59%. In this regard, Rosen et al (2013) examined whether adding a telephone care management protocol to usual continuing care improved patients’ outcomes in the year after discharge from residential mental health treatment; over one-half of study participants had co-occurring mental health and substance use disorders. They found no differences in substance use, psychiatric symptoms, time to first outpatient visit or rehospitalization, or number of outpatient visits between patients who received telephone care management and usual care at four months or one year postdischarge.…”
Section: Discussionmentioning
confidence: 99%